Absence of an effect of high nitrate intake from beetroot juice on blood pressure in treated hypertensive individuals: a randomized controlled trial - Bondonno, Catherine P; Liu, Alex H; Croft, Kevin D; Ward, Natalie C; Shinde, Sujata; Moodley, Yuben; Lundberg, Jon O; Puddey, Ian B; Woodman, Richard J; Hodgson, Jonathan M (The American journal of clinical nutrition, 2015)
Dietary nitrate, which is in green leafy vegetables and beetroot, decreases blood pressure through the enterosalivary nitrate-nitrite-nitric oxide pathway in healthy individuals. Whether similar effects would occur in individuals with treated hypertension and, therefore, at increased risk of cardiovascular disease is unclear. We assessed whether increased dietary nitrate intake by using beetroot juice for 1 wk lowers blood pressure in treated hypertensive men and women. Participants (n = 27) were recruited to a randomized, placebo-controlled, double-blind crossover trial. The effect of 1-wk intake of nitrate-rich beetroot juice was compared with 1-wk intake of nitrate-depleted beetroot juice (placebo). The primary outcome was blood pressure assessed by measuring home blood pressure during the intervention and 24-h ambulatory blood pressure on day 7 of the intervention. Other outcomes included nitrate metabolism assessed by measuring nitrate and nitrite in plasma, saliva, and urine. Relative to the placebo, 1-wk intake of nitrate-rich beetroot juice resulted in a 3-fold increase in plasma nitrite and nitrate, a 7-fold increase in salivary nitrite, an 8-fold higher salivary nitrate, and a 4-fold increase in both urinary nitrite and nitrate (P < 0.001). However, no differences in home blood pressure and 24-h ambulatory blood pressure were observed with 1-wk intake of nitrate-rich beetroot juice in comparison with the placebo. An increase in dietary nitrate intake may not be an effective short-term approach to further lower blood pressure in treated hypertensive subjects.